Time-dependent regulation of morphological changes and cartilage differentiation markers in the mouse pubic symphysis during pregnancy and postpartum recovery - Castelucci, Bianca Gazieri; Consonni, Sílvio Roberto; Rosa, Viviane Souza; Sensiate, Lucimara Aparecida; Delatti, Paula Cristina Rugno; Alvares, Lúcia Elvira; Joazeiro, Paulo Pinto (PLOS ONE, 2018)
Animal models commonly serve as a bridge between in vitro experiments and clinical applications; however, few physiological processes in adult animals are sufficient to serve as proof-of-concept models for cartilage regeneration. Intriguingly, some rodents, such as young adult mice, undergo physiological connective tissue modifications to birth canal elements such as the pubic symphysis during pregnancy; therefore, we investigated whether the differential expression of cartilage differentiation markers is associated with cartilaginous tissue morphological modifications during these changes. Our results showed that osteochondral progenitor cells expressing Runx2, Sox9, Col2a1 and Dcx at the non-pregnant pubic symphysis proliferated and differentiated throughout pregnancy, giving rise to a complex osteoligamentous junction that attached the interpubic ligament to the pubic bones until labour occurred. After delivery, the recovery of pubic symphysis cartilaginous tissues was improved by the time-dependent expression of these chondrocytic lineage markers at the osteoligamentous junction. This process potentially recapitulates embryologic chondrocytic differentiation to successfully recover hyaline cartilaginous pads at 10 days postpartum. Therefore, we propose that this physiological phenomenon represents a proof-of-concept model for investigating the mechanisms involved in cartilage restoration in adult animals.